Effect of Genotype and Density on the Productivity of Mungbean - Yeasmin, R; Karim, MA; Haque, MM; Mia, MAB (Bangladesh Agronomy Journal, 2016)
An investigation was carried out at the experimental field of the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during September to November 2014 to evaluate the productivity of three mungbean genotypes, viz., GK-24 (G1), GK-63 (G2) and BU mug 4 (G3) under four plant spacing (densities) such as i) 15 cm x 10 cm= 66 plants m-2 (D1), ii) 20 cm x 10 cm= 50 plants m-2 (D2), iii) 25 cm x 10 cm= 40 plants m-2 (D3) and iv) 30 cm x 10 cm=33 plants m-2 (D4). The experiment was conducted in a factorial randomized complete block design with three replications. A wide variation among the genotypes was observed in relation to light transmission, yield, and yield contributing characters. At 30 cm x 10 cm spacing (D4) the highest light transmission ratio (LTR) was observed in G1 genotype (57.92) and the lowest LTR value in G2 genotype (46.92). Among the three genotypes, G1 produced the highest seed yield (1094 kg ha-1). But highest seed number pod-1 was found in D2 (11.61) while maximum pods plant-1 (11.08) was in D4 treatment followed by D3 (10.59). Among the four plant densities, treatment D3 showed the highest 1000-seed weight (50.30 g). The highest seed yield (1114 kg ha-1) was recorded in the treatment D4. Among the interaction, the highest number of seeds pod-1 (12.20) was found in the treatment D1G3, though the highest number of pods plant-1(12.03) was in treatment D4G1 but the1000-seed weight was the highest (51.92 g) in D3G1. The highest seed yield (1230 kg ha-1) was recorded from treatment D4G1. The result showed that GK 24 genotype performed the best in all respects of yield and yield attributes at 30 cm x 10 cm spacing compared to other treatments. Bangladesh Agron. J. 2016, 19(1): 11-17